Pertanggungjawaban Pidana atas Penyebaran Konten Kekerasan Diplatfrom Roblox di Indonesia - Sapitri, Wahyuni; Hafrida; Erwin (AL-SULTHANIYAH, 2026)
The development of online gaming platforms based on user-generated content, such as Roblox, has created broad opportunities for user creativity while simultaneously raising legal issues related to the dissemination of violent content. This study aims to analyze the regulation of criminal liability for the dissemination of violent content on digital game platforms, particularly Roblox, and to examine the Indonesian positive law framework related to this issue. The research employs a normative legal method using statutory, conceptual, and comparative approaches through library-based legal research. The results indicate that Indonesian positive law does not specifically regulate the dissemination of violent content on online game platforms, but such conduct may still fall under general provisions of the Criminal Code, the Electronic Information and Transactions Law, and regulations on electronic system providers. The study also finds normative gaps and potential multi-interpretation in law enforcement practices, highlighting the need for harmonization and more adaptive legal reforms to ensure effective legal protection.